APPLICATION OF FILLED DISPERSIONS OF WATER-SOLUBLE POLYMERS FOR FUNCTIONALIZATION OF FIBROUS MATERIALS - ПЛАВАН, В. П.; ІЩЕНКО, О. В.; ТАРАСЕНКО, Н. В.; БУДАШ, Ю. О.; КОЛОДІЙ, А. І. (Technologies and Engineering, 2023)
Purpose. Determination of the influence of the type and concentration of the polymer binder and the amount of introduced adsorbent on the rheological characteristics of filled polymer dispersions and the physical and mechanical properties of combined fibrous materials for water purification technologies. Methodology. As a basis for obtaining fibrous sorption materials in the work, a needle-punched non-woven material with a surface density of 227 g/m2 (PU/PA-6.6) obtained from elastic fibrous waste of the textile industry was used. To increase the sorption capacity of materials, montmorillonite-type clay powder was introduced in an amount of up to 5 and 10% by mass. Polyvinyl alcohol and starch were chosen as water-soluble polymers for impregnating the fibrous base. The influence of the concentration of polymer solutions on the rheological characteristics of filled polymer dispersions was studied. The rheological properties of the filled polymer compositions were determined using a rotary viscometer NDJ-9S (China). The mechanical characteristics of nonwoven materials were determined on a PM-30 type breaking machine, in accordance with the standard DSTU ISO 9073-3:2003. Findings. It was established that the concentration of the polymer binder and the amount of mineral sorbent affect the surface density of fibrous materials impregnated with dispersions of starch and PVA. The introduction of clay up to 10% of the mass of the binder leads to a significant increase in the surface density of fibrous materials. At the same time, there is a decrease in their strength. Applying the filled dispersion of PVA leads to a decrease in the breaking load almost by half with an increase in the amount of added clay. The breaking load decreases by almost a quarter with an increase in the amount of added clay in starch solutions of higher concentration. The application of 3% PVA dispersion or 2-3% starch dispersion with the added of 5% clay minerals provides sufficiently elastic fibrous materials with good strength properties. And taking into account the previously obtained results that the treatment of the fibrous base by 3% dispersions of PVA and starch filled with clay minerals helps to increase the sorption capacity of the obtained materials, these fibrous composites for water treatment technologies can be recommended. Originality. Rational conditions for obtaining filled polymer dispersions with the necessary rheological properties for impregnation of non-woven materials based on fibrous waste to obtain fibrous composites with sorption properties with appropriate physical and mechanical properties were determined. Practical value. Sorption materials obtained on the basis of fibrous waste PU/PA-6,6, impregnated with filled dispersions of water-soluble polymers, can be used in the future for the purification of wastewater of chemical industry enterprises from heavy metals ions, which can be important for the protection of the environment and people’s health.